Commitment as a Mediating Variable: Is There an Influence of Work Experience and Teacher Performance Motivation? - Patraini, Friska Septriyanda; Erlina, RR; Mardiana, Nova (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
The purpose of this study was to determine the effect of work experience and motivation on teacher performance with commitment as a mediating variable for teachers of SMA Negeri in Bandar Lampung City. This research method is quantitative and analyzed using Structural Equation Modeling (SEM) analysis. Data used in the study this obtained from results testing questionnaire against 224 teachers at State High Schools in Bandar Lampung City who were used sample in study with technique purposive sampling. The results obtained from study This support proposed hypothesis that is experience Work influential positive and significant to performance, motivation influential positive and significant to performance, commitment mediate influence experience Work to performance and commitment mediate influence motivation to performance. Implications from study this is so that teachers can increase performance through experience work and work for produce quality work in accordance with criteria that have been determined at school. Apart from that, it is hoped that school principals can increase teacher work motivation using the method of assessing the work of teachers who have completed their assignments. Then by giving appreciation to other teachers, it is hoped that teachers can improve interpersonal relationships, so that teachers feel comfortable and connected. between teachers is increasingly harmonious, with conditions that can improve teacher performance. And, hopefully to head school for can increase teachers' commitment to advance school with method make attachment with the teacher so the teacher will feel become part family at school. Lastly, teachers should do more increase its independence in Work although no there is supervision from head school and able finish task without must wait help colleague work.